Corruption within a cooperative society - Michael Kosfeld (Institute for Advanced Studies (IHS), 1997)
In this paper we take up a model of Okada (1996) to describe the possibility of collective cooperation in a n-person Prisoner's Dilemma game by means of institutional arrangements. In addition, we introduce the possibility to corrupt the institutional authority by paying him some positive transfer in order not to be punished in case of defection. It is shown that there exists a maximal number of corrupting and defecting agents such that the organization is still formed and the rest of the population cooperates.
Keywords: C72; 330; corruption; cooperation; prisoner's dilemma; organization; Korruption; Gefangenendilemma; Spieltheorie; Theorie